Revealing the elasticity of an individual aortic fiber during ageing at nanoscale by in situ atomic force microscopy. Issue 2 (5th January 2021) - Berquand, Alexandre; Wahart, Amandine; Henry, Aubéri; Gorisse, Laetitia; Maurice, Pascal; Blaise, Sébastien; Romier-Crouzet, Béatrice; Pietrement, Christine; Bennasroune, Amar; Sartelet, Hervé; Jaisson, Stéphane; Gillery, Philippe; et al.
Abstract : Atomic Force Microscopy imaging allows to correlate at high resolution local changes in the structure and the elastic properties of elastin fibers and of the surrounding matrix for mice aorta cross sections. Abstract : Arterial stiffness is a complex process affecting the aortic tree that significantly contributes to cardiovascular diseases (systolic hypertension, coronary artery disease, heart failure or stroke). This process involves a large extracellular matrix remodeling mainly associated with elastin content decrease and collagen content increase. Additionally, various chemical modifications that accumulate with ageing have been shown to affect long-lived assemblies, such as elastic fibers, that could affect their elasticity. To precisely characterize the fiber changes and the evolution of its elasticity with ageing, high resolution and multimodal techniques are needed for precise insight into the behavior of a single fiber and its surrounding medium. In this study, the latest developments in atomic force microscopy and the related nanomechanical modes are used to investigate the evolution and in a near-physiological environment, the morphology and elasticity of aorta cross sections obtained from mice of different ages with an unprecedented resolution. In correlation with more classical approaches such as pulse wave velocity and fluorescence imaging, we demonstrate that the relative Young's moduli of elastic fibers, as well as those of the surrounding areas, significantly increase with ageing. This nanoscale characterization presents a new view on the stiffness process, showing that, besides the elastin and collagen content changes, elasticity is impaired at the molecular level, allowing a deeper understanding of the ageing process. Such nanomechanical AFM measurements of mouse tissue could easily be applied to studies of diseases in which elastic fibers suffer pathologies such as atherosclerosis and diabetes, where the precise quantification of fiber elasticity could better follow the fiber remodeling and predict plaque rupture.